2021
DOI: 10.3390/molecules26237186
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl Trisulfide, the Antifungal Component of Garlic Essential Oil and the Bioactivity of Its Nanoemulsions Formed by Spontaneous Emulsification

Abstract: The aim of this study was to evaluate the chemical compounds of garlic essential oil (EO), and determine the antifungal efficacy of garlic EO and its major components, diallyl trisulfide and its nanoemulsions against wood-rotting fungi, Trametes hirsuta and Laetiporus sulphureus. GC-MS analysis revealed that the major constituents of garlic EO were diallyl trisulfide (39.79%), diallyl disulfide (32.91%), and diallyl sulfide (7.02%). In antifungal activity, the IC50 value of garlic EO against T. hirsuta and L. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 69 publications
(106 reference statements)
0
5
0
Order By: Relevance
“…Tocmo et al ( 118 ) assert that DATS is more prevalent in fresh GO than commercial oils, with the number of DADS varying depending on the temperature or duration of the extraction process. The amount and number of constituents in essential oils vary, but in all investigations reported diallyl disulfide is almost always the main ingredient followed by allyl disulfide, allyl trisulfide ( 119 ). These substances are the transformation products from allicin, a substance with significant medicinal value because it has a wide range of biological activities.…”
Section: Garlic Essential Oils: Their Composition and Propertiesmentioning
confidence: 99%
“…Tocmo et al ( 118 ) assert that DATS is more prevalent in fresh GO than commercial oils, with the number of DADS varying depending on the temperature or duration of the extraction process. The amount and number of constituents in essential oils vary, but in all investigations reported diallyl disulfide is almost always the main ingredient followed by allyl disulfide, allyl trisulfide ( 119 ). These substances are the transformation products from allicin, a substance with significant medicinal value because it has a wide range of biological activities.…”
Section: Garlic Essential Oils: Their Composition and Propertiesmentioning
confidence: 99%
“…Gong et al reported that garlic essential oil and its compounds diallyl disulfide and diallyl trisulfide showed high toxicity against brown-rot fungus L. sulphureus with IC 50 values of 44.6, 73.2, and 31.6 µg/mL, respectively [ 26 ]. Cinnamaldehyde is a well-known natural antifungal agent; IC 50 values of cinnamaldehyde were 0.17 and 0.65 mM against L. sulphureus and L. betulina , respectively [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…The discussion of DPTTS from onions almost immediately also brings us to its relative in garlic, diallyl trisulfide (C 3 H 5 SSSC 3 H 5 , DATS). Indeed, DATS is equally, if not more active biologically compared to DPTTS and is also the source of centuries of medicinal inspiration and a plethora of publications [ 105 , 106 , 107 ]. Similar to DPTTS, DATS is volatile with a boiling point of 120 °C, and there are numerous anecdotes of DATS and its relatives diallyl disulfide (C 3 H 5 SSC 3 H 5 , DADS, boiling point 187.5 °C) and diallyl tetrasulfide (C 3 H 5 SSSSC 3 H 5 , DATTS, boiling point 45 °C) fuming out entire incubators when applied in Petri dish-based studies [ 11 ].…”
Section: Volatile Natural Productsmentioning
confidence: 99%